Sentidos produzidos sobre a residência multiprofissional por egressos de um programa - Silva, Stephane Juliana Pereira da (2016)
We seek to understand how former residents from the Multiprofessional Residence Program produce meanings about their professional training, according to their discourses on the experience and its relation to the Permantent Education in Health Policy. Our theorethical and methodological approach is Discursive Practices and Meaning Production, which bases on Social Construccionism Movement. To achieve our goal and produce information, we performed a workshop with five former residents of the Multiprofessional Residence Program of Maceió. The participants were two social workers, a psychologist, a nutricionist and a physical therapist. All of them were at the first three Program classes and are employed. The analysis focused on the characteristics of joint action experience according to their discourses about the Program. Results show that dialogue and teamwork, provided by the experience on the Program, are join actions that have made possible to produce new knowl edge and new professional possibilities in health services. Furthermore, Multiprofessional Residence Program has made the emergence of new knowledges and practices possible, working as a training device, in line with Permanent Education in Health Policy.